2022
DOI: 10.3390/jcm11061548
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Family-Centred Early Intervention in Children with Hearing Loss: A Conceptual Model

Abstract: At least two per thousand newborns are affected by hearing loss, with up to 40% with an additional disability. Early identification by universal newborn hearing screening and early intervention services are available in many countries around the world, with limited data on their effectiveness and a lack of knowledge about specific intervention-related determinants of child and family outcomes. This concept paper aimed to better understand the mechanisms by which multi-dimensional family-centred early intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 173 publications
(215 reference statements)
0
8
0
1
Order By: Relevance
“…Similarly, patients with CND were arbitrarily categorized into the syndromic SNHI group (e.g., two patients with CHARGE syndrome had CND) and the CND group according to the presence of specific symptoms or signs, yet the CI outcome in the syndromic CND patients might be influenced by the CND to a larger extent than the “syndrome” per se . Third, as this study investigated a longitudinal cohort with patients recruited from two different CI centers for more than ten years, certain surgical factors (e.g., the adoption of soft surgery and the preservation of residual hearing) [ 52 , 53 ] and early intervention strategies [ 21 ] related to CI outcomes could not be ascertained in every subject and were not included in the analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, patients with CND were arbitrarily categorized into the syndromic SNHI group (e.g., two patients with CHARGE syndrome had CND) and the CND group according to the presence of specific symptoms or signs, yet the CI outcome in the syndromic CND patients might be influenced by the CND to a larger extent than the “syndrome” per se . Third, as this study investigated a longitudinal cohort with patients recruited from two different CI centers for more than ten years, certain surgical factors (e.g., the adoption of soft surgery and the preservation of residual hearing) [ 52 , 53 ] and early intervention strategies [ 21 ] related to CI outcomes could not be ascertained in every subject and were not included in the analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to accurately predict outcomes is the first step in developing individualized management to enhance CI outcomes in hearing-impaired children. Multidimensional family-centered early intervention in hearing-impaired children is also recommended, as it is proven to be one major driver of CI outcomes [ 21 ]. Although research in the past decades has identified several prognostic factors, there is still no reliable prediction tool for clinical use, probably due to the heterogeneous etiologies of pediatric SNHI and the lack of integrated clinical data.…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, every child with a pure-tone average (PTA) of 20 dB HL or higher should be identified, as even mild hearing loss can affect educational attainment (Moore et al, 2019). Identification of hearing loss allows for the provision of support and intervention, which has proven to have positive effects on the development of those children (Holzinger et al, 2022; Moeller, 2000; Pimperton et al, 2016; Watkin et al, 2007; Yoshinaga-Itano et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Vocabulary quotients were calculated by dividing the child’s expressive vocabulary age by his/her chronological age and multiplying by 100. Factors that have been shown to affect language outcomes in children with HL are audiological (the degree of HL unaided and aided), cognitive (nonverbal intelligence and executive functioning), intervention- and family-related (age at fitting with hearing aids, age at cochlear implantation, age at enrollment in early intervention and quality and quantity of family–child interactions) [ 23 ]. Even though GJB2 mutations are the most common genetic cause of HL in children, little is known about the clinical characteristics and language outcomes in population-oriented populations including children with different degrees of HL (users of hearing aids and cochlear implants) and impacts of specific genotypes on language outcomes.…”
Section: Introductionmentioning
confidence: 99%